Achieving Marketing Lending Targets in the Perspective of Islamic Business Economics (A Study of BMT Assyafi'iyah Berkah Nasional Pekalongan) - Alimuddin, Agus; Imanda Putra, Alfiansyah; Alfiani Saputri, Ari; Kurniawati, Devy; Damayanti, Novita (Program Studi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam UIN Datokarama Palu, 2023)
Currently, competition among financial institutions is becoming stronger in completing business activities; each financial company is doing everything they can to maintain their business presence in the eyes of the public by attracting buyers' attention and striving as much as possible. It is hoped that they can further develop administration to buyers. In this condition, the showcase area has a good relationship with human resources that become agents of promotional activities. Advertising in completing work in sharia financial institutions will determine the focus of achievements that must be made. The purpose of this research is to find out the achievement of marketing lending targets from the perspective of Islamic business economics present at BMT Assyafi’yah Berkah Nasional Pekalongan. This type of research is a field study that uses a subjective inquiry strategy. The type of research is qualitative descriptive research. The means of information investigation are information search, information disclosure, and objectives and confirmation. The final results of this research show that the behavior of workers in achieving advertising focus at BMT Assyafi'iyah Berkah Nasional Pekalongan has been implemented and is in accordance with the 4P methodology, namely: product technique, cost procedure, place system, and progress system. Meanwhile, representative behavior in achieving display targets is in accordance with Islamic business ethics which consists of 5 standards, namely obligation, fairness, unity, unlimited choice, and balance